2021
DOI: 10.1155/2021/9916927
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Safety of Mark-Guided Submucosal Tunneling Endoscopic Resection for Treatment of Esophageal Submucosal Tumors Originating from the Muscularis Propria: A Single-Center Retrospective Study

Abstract: Background. Submucosal tunneling endoscopic resection (STER) has effectively removed esophageal submucosal tumors (SMTs) originating from the muscularis propria (MP) layer. However, clinical failure and adverse events of STER remain concerned. In this study, we described a mark-guided STER (markings before creating entry point) and evaluated its feasibility and safety for esophageal SMTs originating from MP. Methods. Patients receiving the mark-guided STER from October 2017 to July 2020 were included and follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Стоит отметить, что при полнослойном дефекте стенки пищевода возможность герметичного закрытия доступа в тоннель при помощи эндоскопических клипс позволяет минимизировать риски послеоперационных осложнений, что является основным преимуществом данной методики. Как правило, риск развития послеоперационных осложнений имеет прямую зависимость от размера и конфигурации новообразования [24].…”
Section: Discussionunclassified
“…Стоит отметить, что при полнослойном дефекте стенки пищевода возможность герметичного закрытия доступа в тоннель при помощи эндоскопических клипс позволяет минимизировать риски послеоперационных осложнений, что является основным преимуществом данной методики. Как правило, риск развития послеоперационных осложнений имеет прямую зависимость от размера и конфигурации новообразования [24].…”
Section: Discussionunclassified
“…This avoids any irritation from gastric reflux, thus reducing the incidence of delayed bleeding. [ 3 , 28 ] In a randomized controlled trial, it was noted that the lack of a plasma membrane layer can easily cause perforation after the resection of deeper intrinsic esophageal myxomatous tumors; furthermore, owing to a narrower esophageal lumen and greater wall tension in such cases, titanium clips cannot completely and effectively close the perforation, making the individuals prone to developing postoperative complications and even requiring surgical intervention. [ 29 ] Studies have shown that the application of some new methods and materials, for example, a newly invented injectable “thermogel as a novel submucosal injectable substance can reduce the incidence of complications in ESD.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 , 9 ] Anxiety and frustration, lack of knowledge, and financial challenges are major barriers that keep patients from availing cancer prevention treatments, thus leading to rapid progression of the disease. [ 3 ] Therefore, endoscopic techniques are currently preferred over surgical resection of submucosal esophageal tumors. This study investigates two endoscopic techniques, one of which is endoscopic submucosal dissection (ESD), which is a commonly used method for treating SMT.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations